OBJECTIVE AND SUBJECTIVE IN AN ASSESSMENT OF THE DANGER OF THE CONSEQUENCES OF PEACEFUL NUCLEAR EXPLOSIONS ON THE EXAMPLE OF FACILITY «DNEPR» - E. V. Hramcov; K. V. Varfolomeeva; S. A. Zelencova; G. V. Arhangel’skaja; V. S. Repin; N. M. Vishnjakova (Радиационная гигиена)
The purpose of research was to assess the dynamics of the changes during the five-year period (from 2008 to 2013) of the radiation situation in the territory adjacent to the places of the peaceful nuclear explosions of the “Dnepr” series in the Murmansk region, the analysis of information environment of the subject in the Internet and the study of the population public opinion.Gamma-radiation dose rate registered in the investigated territory in 2013 (140 – 180 nSv/h) corresponded to the natural radiation background, characteristic for the Khibiny. The average content of 137Cs in soil is comparable to the level of the global fallout contamination. Levels of the artificial radionuclides concentration in the samples of natural foodstuffs (mushrooms and berries) were found in 2013 to be much lower than corresponded permissible levels. Values of the 3H specific activity for the water samples from the surface and underground sources sampled in 2013 decreased more than in 1,5 times in comparing with 2008 and have not exceeded the interventional level – 7600 Bq/kg. Exposure doses estimated for the critical group of population Exposure doses estimated in 2013 for the critical groups of population have not exceeded the dose limit adopted in RSS-99/2009. The interest of population to the mentioned problem has not been pointed out on the basic of the analysis of publications electronic versions in mass media for 2013. The comparative analysis of the results of the survey showed that level of public concern over the radiation environment in their places of residence has been low in 2008 and even lower in 2013. With a low level of the knowledge concerning radiation respondents found their significant interest for the issues relating radiation, its effects on the health and radiation protection measures.Along with the radiation-hygienic monitoring, it is necessary to conduct regular activities aimed on the population informing about the radiation situation on the basic of the significant data obtained from the responsible agencies specialists.